Determination of the Phenolic Composition and Antioxidant Activity of Pear Extracts. (12th November 2017) - Liaudanskas, Mindaugas; Zymonė, Kristina; Viškelis, Jonas; Klevinskas, Almantas; Janulis, Valdimaras
Abstract : The specific HPLC analytical procedure was developed and validated for the determination of phenolic compounds in pear samples of different popular cultivars "Conference, " "Concordia, " "Grabova, " and "Patten." HPLC mobile phase consisted of 0.05% (v/v) trifluoroacetic acid in water and 100% (v/v) acetonitrile. The HPLC method was used to identify and confirm the specificity of 8 analytes: chlorogenic acid, rutin, hyperoside, isoquercitrin, isorhamnetin rutinoside, quercitrin, quercitrin malonyl glucoside, and isorhamnetin glucoside. Repeatability % RSD did not exceed 3.87%, and intermediate precision did not exceed 4.63%. The total content of phenolic compounds varied from 0.51 ± 0.001 mg/g (cv. "Concordia") to 1.11 ± 0.013 mg/g (cv. "Patten"). Chlorogenic acid was the major component in all the tested pear cultivars. The highest amount of chlorogenic acid (0.69 ± 0.033 mg/g) was found in pear samples of the cultivar "Grabova, " and the highest amount of flavonol compounds (1.11 ± 0.013 mg/g) was found in pear samples of the cultivar "Concordia."